Acid precipitation followed by microalgae (Chlorella vulgaris) cultivation as a new approach for poultry slaughterhouse wastewater treatment. (September 2021) - Terán Hilares, Ruly; Garcia Bustos, Kiara A.; Sanchez Vera, Fabio P.; Colina Andrade, Gilberto J.; Pacheco Tanaka, David A.
Graphical abstract: Highlights: About 80% of CODT was removed from PSW by acid precipitation at pH 4. PSW treated by acid precipitation was used as medium for microalgae cultivation. Microalgae cultivation in a continuous mode remove 83% of residual COD from PSW. The water obtained after membrane filtration allows safe disposal. Abstract: Poultry slaughterhouse wastewater (PSW) contains high organic matter and nutrients requiring thus a special treatment before its final disposal. In this work, acid precipitation (H2 SO4 ) followed by microalgae " Chlorella vulgaris" cultivation both in batch and continuous processes was studied as an alternative method for PSW treatment. By reducing the pH value of PSW from 6 to 7 to 4, about 80% of the total chemical oxygen demand (CODT ) was removed as sludge. In the supernatant, the COD residual was efficiently removed (83%) by microalgae in the batch process, using an internal-loop concentric tube photobioreactor (4.5 L). Moreover, in continuous process, after 89 h, the COD value resulted lower than 200 mg L -1 and 1.2 g L -1 of microalgae in the output line. The proposed PSW treatment method is promising from economic and environmental viewpoints, since the microalgal biomass can be valued in a biorefinery context.